ANALYSIS OF MANGROVE COVER AND DENSITY CHANGES BASED ON NDVI IN THE COASTAL AREA OF SOUTH LAMPUNG REGENCY, 2020–2023 - Lalik Salistia Citra; Muliawati Handayani; Mulkan Nuzapril (Universitas Mataram, 2026)
Mangrove ecosystems are an essential component of coastal areas, providing ecological, physical, and socio-economic functions. Mangroves play a crucial role in protecting coastlines from abrasion, reducing wave energy, and providing habitats for various aquatic organisms. Changes in mangrove cover over time reflect environmental pressures as well as the effectiveness of management and rehabilitation efforts in a particular region. This study aims to analyze changes in mangrove cover in the coastal area of South Lampung Regency during the period 2020–2023 using a spatial and multitemporal approach based on satellite imagery. The data used consist of Landsat 8 OLI/TIRS imagery from 2020 to 2023, which were analyzed using the Normalized Difference Vegetation Index (NDVI). The analysis was conducted to identify the distribution, extent, and dynamics of changes in mangrove cover and density spatially and temporally. The results indicate that mangrove cover in the coastal area of South Lampung Regency showed an increasing trend during the observation period, although pressures from coastal activities were still identified in several locations. Variations in NDVI values reflect differences in mangrove density ranging from low to high, indicating diverse mangrove vegetation conditions. The information generated from this study is expected to support sustainable mangrove management and conservation planning in the coastal area of South Lampung Regency.